The effects of substituting Sn for Ni on the thermal and some other characteristics of NiTiSn shape memory alloys - Qader, Ibrahim Nazem; Kok, Mediha; Cirak, Zehra Deniz (Springer, 2021)
In this study, the thermal stability and phase transformation of Ni50-xTi50Snx (x = 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, and 3.5 at%) SMAs have been investigated. Some thermal, mechanical, and microstructural characteristics were measured using DSC, Vickers microhardness, XRD, and SEM-EDX devices. Calculations, such as grain size and entropy change, were also performed based on the DSC results. It is found that by increasing the amount of Sn in NiTiSn alloy, fragmentation has occurred in the alloy, which may be due to the high concentration of Sn and Ti in the grooves. Furthermore, the microhardness and grain size are in harmony, i.e., the microhardness of the alloys was influenced by the grain size. Additionally, martensite and austenite peaks were shifted to the lower temperature by increasing the cycling process, while the rate of shifting increased generally by adding more Sn element into the alloy.
Keywords: Shape memory alloys; NiTiSn; Thermal stability; Ti2Ni; Vickers microhardness